Neoadjuvant Treatment Is Not Associated with Better Survival in T4 Non-Small Cell Lung Cancer - Gizem Özçıbık Işık; İsmail Sarbay; Halil İbrahim Bulut; Burcu Kılıç; Ezel Erşen; H. Volkan Kara; M. Kamil Kaynak; Akif Turna (Cerrahpaşa Medical Journal)
Objective: The best treatment strategy for T4 non-small cell lung cancer (NSCLC) has yet to be defined. However, studies have shown that surgical resection benefits selected patients without N2/N3 disease. We aimed to determine the effect of neoadjuvant chemotherapy and/or radiation therapy on survival in patients with T4N0-1 NSCLC.